Uncompensated care before and after prospective payment: the role of hospital location and ownership. - Hultman, C I (1991)
Research was undertaken to determine the effects of hospital ownership, location, and Medicare's prospective payment system (PPS) on inpatient uncompensated care. A nonequivalent group design was used with repeated measures of uncompensated care (UNCC) on 137 system hospitals taken pre- and post-PPS. Investor-owned system hospitals demonstrated the largest increase in UNCC (37 percent) under the PPS. Results suggest that not-for-profit and investor-owned system hospitals are becoming more similar in levels of uncompensated care provided and that the PPS has had a negative effect on rural hospital profitability.